# 2X(X^2-4X+7)=

## Simple and best practice solution for 2X(X^2-4X+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2X(X^2-4X+7)= equation:

Simplifying
2X(X2 + -4X + 7) = 0

Reorder the terms:
2X(7 + -4X + X2) = 0
(7 * 2X + -4X * 2X + X2 * 2X) = 0
(14X + -8X2 + 2X3) = 0

Solving
14X + -8X2 + 2X3 = 0

Solving for variable 'X'.

Factor out the Greatest Common Factor (GCF), '2X'.
2X(7 + -4X + X2) = 0

Ignore the factor 2.
Subproblem 1Set the factor 'X' equal to zero and attempt to solve:

Simplifying
X = 0

Solving
X = 0

Move all terms containing X to the left, all other terms to the right.

Simplifying
X = 0
Subproblem 2Set the factor '(7 + -4X + X2)' equal to zero and attempt to solve:

Simplifying
7 + -4X + X2 = 0

Solving
7 + -4X + X2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-7' to each side of the equation.
7 + -4X + -7 + X2 = 0 + -7

Reorder the terms:
7 + -7 + -4X + X2 = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -4X + X2 = 0 + -7
-4X + X2 = 0 + -7

Combine like terms: 0 + -7 = -7
-4X + X2 = -7

The X term is -4X.  Take half its coefficient (-2).
Square it (4) and add it to both sides.

Add '4' to each side of the equation.
-4X + 4 + X2 = -7 + 4

Reorder the terms:
4 + -4X + X2 = -7 + 4

Combine like terms: -7 + 4 = -3
4 + -4X + X2 = -3

Factor a perfect square on the left side:
(X + -2)(X + -2) = -3

Can't calculate square root of the right side.

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.SolutionX = {0}`